2012
DOI: 10.1159/000341990
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides and Skin: A Paradigm of Translational Medicine

Abstract: Antimicrobial peptides (AMPs) are small, cationic, amphiphilic peptides with broad-spectrum microbicidal activity against both bacteria and fungi. In mammals, AMPs form the first line of host defense against infections and generally play an important role as effector agents of the innate immune system. The AMP era was born more than 6 decades ago when the first cationic cyclic peptide antibiotics, namely polymyxins and tyrothricin, found their way into clinical use. Due to the good clinical experience in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 181 publications
0
43
0
Order By: Relevance
“…Interestingly, both epithelial cells and neutrophils can produce LL-37 or CRAMP. These extracellular AMPs possess a broad spectrum of antimicrobial activity by inducing pore formation in the bacterial membrane and represent a potent first line of host defense (11,14). The strong antibacterial activity of AMPs has selected many bacterial species to evolve countermeasures for evading the same defense mechanism (15-17).…”
mentioning
confidence: 99%
“…Interestingly, both epithelial cells and neutrophils can produce LL-37 or CRAMP. These extracellular AMPs possess a broad spectrum of antimicrobial activity by inducing pore formation in the bacterial membrane and represent a potent first line of host defense (11,14). The strong antibacterial activity of AMPs has selected many bacterial species to evolve countermeasures for evading the same defense mechanism (15-17).…”
mentioning
confidence: 99%
“…The triple combination used in this trial not only offers pain relief due to the sodium channel blocking agent benzocaine, but also antiviral and antimicrobial activity due to benzalkonium chloride and tyrothricin. The antiviral activity for benzalkonium chloride, as well as the antibacterial and antiviral property of tyrothricin, is known 18, 19, 20. Antiviral properties for the combination of all three compounds in Dorithricin ® have been recently confirmed in an in vitro model 21.…”
Section: Discussionmentioning
confidence: 99%
“…The authors tested Gram‐positive bacteria and yeast strains which all turned out to be highly susceptible to tyrothricin (MICs ≤ 4 mg/L), despite decade‐long use of the substance. The authors concluded, “No acquired resistance of the tested strains was determined.”54 Also, the topical usage on mucous membranes reviewed by Korting19 concluded, “in contrast to other antibiotics, AMPs (such as tyrothricin)” do not seem to propagate the development of antibiotic‐resistant micro‐organisms.”19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foremost clinical features of psoriasis include a typical hyper-proliferation and abnormal differentiation of keratinocytes, which is associated with the excessive production of pro-inflammatory cytokines/chemokines and activated T cells and plasmacytoid dendritic cells (pDCs) 82) . The psoriatic skin produces almost all well-known AMPs/HDPs, including hBD-1, hBD-2, hBD-3, LL-37, S100A7, S100A8, S100A9, S100A15, RNase 7, lysozyme, elafin and SLPI 1) 2) .…”
Section: Amps/hdps In Psoriasismentioning
confidence: 99%